(untitled) (Translation: The University of Toledo Journal of Medical Sciences, 2022)
The effect of cocaine use on the cerebral vasculature is well understood, with potential for ischemic or hemorrhagic stroke. The risk of adverse effects can be prolonged and amplified in patients with renal dysfunction and uremia. Uremia-induced osmotic gradients and upregulation of aquaporin channels along with cocaine-induced blood-brain barrier degradation may act synergistically. We present the first known case of a non-compliant dialysis patient who suffers cerebral edema, tonsillar herniation, and brain death following cocaine use. A 32-year-old female with end-stage renal disease presented with shortness of breath and flu-like symptoms for one week and was alert and oriented with no neurologic deficits. The patient had missed her last 5 dialysis treatments and labs revealed hyperkalemia and uremia. Urine drug screen was positive for cocaine, opiates, and tetrahydrocannabinol (THC). Following dialysis and metabolic correction, she developed an irregular respiratory pattern and stridor and received neck computed tomography (CT). The patient became unresponsive with dilated and nonreactive pupils. CT revealed absent intraluminal carotid and vertebral artery flow at the skull base, cerebellar tonsil herniation, and anoxic brain injury. Vital signs were maintained, and cerebral edema was managed with 45-degree head-of-bed elevation and mannitol. Following cerebral edema treatment, the patient had preserved respiratory drive, fixed and dilated pupils, no corneal reflex, no cough or gag reflex, and negative oculocephalic reflex. Repeat cranial CT angiography revealed bilateral hemispheric edema, basal subarachnoid hemorrhage, and confirmed absent intracranial blood flow. Brain death was diagnosed with a radioisotope cerebral blood flow study. The use of cocaine in patients with renal dysfunction may increase the risk of cerebral edema and tonsillar herniation due to synergistic physiologic effects. Physicians should be aware of this interaction to allow for preventative measures.